2022
DOI: 10.1111/iju.14813
|View full text |Cite
|
Sign up to set email alerts
|

Importance of considering interest in sex when evaluating satisfaction after robot‐assisted radical prostatectomy

Abstract: Objectives To assess the impact of patients’ interest in sex on the satisfaction after robot‐assisted radical prostatectomy, longitudinal changes of urinary and sexual functions and bothers were evaluated. Methods A total of 101 patients underwent robot‐assisted radical prostatectomy in our institution. Based on sexual interest, they were divided into the high‐interest and low‐interest groups. Overall satisfaction, urinary function, urinary bother, sexual function, and sexual bother were evaluated using the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…On the other hand, only urinary trouble affected satisfaction after RARP in patients with a low-interest in sex. 5 In the present study, two points were of special interest. First, in the high-interest in sex group, sexual trouble was prolonged after RARP in dissatisfied patients regardless of improvement in sexual function to the same degree as in satisfied patients.…”
Section: Editorial Commentmentioning
confidence: 81%
See 4 more Smart Citations
“…On the other hand, only urinary trouble affected satisfaction after RARP in patients with a low-interest in sex. 5 In the present study, two points were of special interest. First, in the high-interest in sex group, sexual trouble was prolonged after RARP in dissatisfied patients regardless of improvement in sexual function to the same degree as in satisfied patients.…”
Section: Editorial Commentmentioning
confidence: 81%
“…[1][2][3][4] In the present study, Kohada et al divided patients who underwent RARP into a high-interest in sex group and a lowinterest in sex group on the basis of attempts for penile rehabilitation. 5 The authors evaluated urinary function, urinary trouble, sexual function, and sexual trouble using the expanded prostate cancer index composite questionnaire. 5 The study showed that both urinary trouble and sexual trouble affected the postoperative satisfaction of patients with a highinterest in sex.…”
Section: Editorial Commentmentioning
confidence: 99%
See 3 more Smart Citations